2013
DOI: 10.1111/jth.12168
|View full text |Cite
|
Sign up to set email alerts
|

A critical role of thrombin/PAR-1 in ADP-induced platelet secretion and the second wave of aggregation

Abstract: Summary. Background: The stable or second wave of platelet aggregation often observed in ADP-stimulated platelet-rich plasma (PRP) with an artificially lowered extracellular calcium level has been attributed to enhanced thromboxane A 2 (TXA 2 ) generation and inhibition of ectonucleotidase activity. However, the role of thrombin in ADP-induced platelet secretion and the second wave of aggregation is unknown. Objectives and Methods: We employed aggregometry, flow cytometry, immunoblotting and ELISA to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
1
15
0
1
Order By: Relevance
“…Recently, Jiang and colleagues demonstrated that platelets activated with ADP generate thrombin, which propagates platelet activation through thrombinmediated PAR1 activation. 42 Platelets exposed to anticoagulants prior to activation with ADP also exhibit impaired thrombin/ PAR1 signaling. Therefore, PAR1 antagonists may represent a novel therapeutic target for regulation of tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Jiang and colleagues demonstrated that platelets activated with ADP generate thrombin, which propagates platelet activation through thrombinmediated PAR1 activation. 42 Platelets exposed to anticoagulants prior to activation with ADP also exhibit impaired thrombin/ PAR1 signaling. Therefore, PAR1 antagonists may represent a novel therapeutic target for regulation of tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 In addition, thrombin is also generated in response to platelet activation by the agonist adenosine 59-diphosphate (ADP), which results in subsequent activation of the PAR1 receptor. 42 Therefore, anticoagulants could impact tumor cell and platelet interaction by inhibiting thrombin and interfering with PAR-mediated platelet activation. The importance of PAR blockade in angiogenesis was previously demonstrated by Ma and colleagues, who showed that PAR1 inhibition diminished angiogenic-dependent wound healing.…”
mentioning
confidence: 99%
“…Several stimulators of platelet activation have been reported, including ADP and LTC 4 . 37,38 Both P2Y12 and CysLTR1 are involved in the PI3K/Akt pathway, 36,40 which strongly suggests the synergistic effects of the two respective antagonists Clo/Mon. We could not demonstrate the effects of LTC 4 on platelet activation, which were demonstrated previously, 35 possibly due to the prolonged activation of platelets during the induction period in our asthma mouse F I G U R E 7 Correlations between platelet-eosinophil aggregations (PEA) and eosinophil counts with inflammatory mediators and leukotriene E4 (LTE 4 ).…”
Section: Correlation Of Pea and Eosinophil Count With Inflammatory mentioning
confidence: 98%
“…Adenosine diphosphate is known to stimulate platelets thorough a phosphoinositide 3-kinase (PI3K)/Akt-dependent pathway. 37,38 Both P2Y12 and CysLTR1 are involved in the PI3K/Akt pathway, 36,40 which strongly suggests the synergistic effects of the two respective antagonists Clo/Mon. P2Y12R antagonists inhibit eosinophil degranulation.…”
Section: Correlation Of Pea and Eosinophil Count With Inflammatory mentioning
confidence: 98%
“…PAR is a subfamily of the seven-pass transmembrane G-protein-coupled receptors, including PAR1, PAR2, PAR3 and PAR4 ( 25 ). PAR1 is expressed on platelets and is activated by thrombin or tissue factor in the tumor microenvironment ( 26 , 27 ). Notably, PAR1 is also expressed in multiple tumor cells, and inhibition of PAR1 may suppress tumor growth and metastasis ( 28 ).…”
Section: Introductionmentioning
confidence: 99%